2004
DOI: 10.1042/bst0320496
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage apoptosis in host immunity to mycobacterial infections

Abstract: Macrophage apoptosis occurs within the granuloma, which is essential for successful immunity to tuberculosis. In vitro macrophage apoptosis is associated with the killing of intracellular Mycobacterium tuberculosis. A greater understanding of these observations will lead to new immunotherapies and improved vaccine design. The relevant apoptotic stimuli, the anti-mycobacterial mechanisms that they stimulate and their physiological relevance are reviewed in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Cell death by apoptosis has been postulated as a potentially important method by which infected macrophages are removed in TB [41]. We therefore examined some of the other factors involved in the FADD pathway of cell death, which is activated by FasL and TNF-a.…”
Section: Assessment Of Production Of Fas and Fasl In Different Clinicmentioning
confidence: 99%
“…Cell death by apoptosis has been postulated as a potentially important method by which infected macrophages are removed in TB [41]. We therefore examined some of the other factors involved in the FADD pathway of cell death, which is activated by FasL and TNF-a.…”
Section: Assessment Of Production Of Fas and Fasl In Different Clinicmentioning
confidence: 99%
“…4 Stimulation of host macrophage apoptosis eliminates a potential site for future proliferation and destroys the infecting bacteria. 5 It has been suggested that phagocytosis of apoptotic bodies, sequestering pathogens, permits more efficient fusion of the phagosome with the lysosome resulting in the digestion of the pathogen. 6 Engulfment of dying macrophages by dendritic cells additionally promotes antigen presentation to T cells, linking innate and adaptive immunity.…”
Section: Significance Of Cell Death During Infectionmentioning
confidence: 99%
“…2,3 Furthermore, apoptotic macrophages are critical for inducing adaptive immune responses, as apoptotic vesicles containing mycobacteria are phagocytized by nearby antigen-presenting cells and presented to CD8 1 T cells. 4,5 Apoptosis of macrophages in this setting is partially tumor-necrosis factor-dependent. 6 Pathogenic MTB is reported to combat apoptosis through various mechanisms, including switching the cell death mode to necrosis and inactivating tumor-necrosis factor signaling.…”
Section: Introductionmentioning
confidence: 99%